Combining ancient DNA and radiocarbon dating data to increase chronological accuracy. (September 2021) - Sedig, Jakob W.; Olalde, Iñigo; Patterson, Nick; Harney, Éadaoin; Reich, David
Abstract: This paper examines how ancient DNA data can enhance radiocarbon dating. Because there is a limit to the number of years that can separate the dates of death of related individuals, the ability to identify relatives through ancient DNA analysis can serve as a constraint on radiocarbon date range estimates. To determine the number of years that can separate related individuals, we modeled maximums derived from biological extremes of human reproduction and death ages and compiled data from historic and genealogical death records. We used these data to jointly study the date ranges of a global dataset of individuals that have been radiocarbon dated and for which ancient DNA analysis identified at least one relative. We found that many of these individuals could have their date uncertainties reduced by building in date of death separation constraints. We examined possible reasons for date discrepancies of related individuals, such as dating of different skeletal elements or wiggles in the radiocarbon curve. We also developed a program, refinedate, which researchers can download and use to help refine the radiocarbon date distributions of related individuals. Our research demonstrates that when combined, radiocarbon dating and ancient DNA analysis can provide a refined and richer view of the past. Highlights: Ancient DNA allows archaeologists to identify individuals that are biologically related. There are biological limitations to the number of years that can separate the death dates of related individuals. We examined how biological relatedness can constrain C14 date ranges with OxCal and a program we developed, refinedate . We examined if applying constraints to a large dataset can reveal dating issues in the archaeological record.